Interplays of different types of epitranscriptomic mRNA modifications - Rengaraj, Praveenkumar; Obrdlík, Aleš; Vukić, Dragana; Varadarajan, Nandan Mysore; Keegan, Liam P; Vaňáčová, Štěpánka; O'Connell, Mary A (RNA biology, 2021)
Eukaryotic mRNAs are modified by several chemical marks which have significant impacts on mRNA biology, gene expression, and cellular metabolism as well as on the survival and development of the whole organism. The most abundant and well-studied mRNA base modifications are m6A and ADAR RNA editing. Recent studies have also identified additional mRNA marks such as m6Am, m5C, m1A and Ψ and studied their roles. Each type of modification is deposited by a specific writer, many types of modification are recognized and interpreted by several different readers and some types of modifications can be removed by eraser enzymes. Several works have addressed the functional relationships between some of the modifications. In this review we provide an overview on the current status of research on the different types of mRNA modifications and about the crosstalk between different marks and its functional consequences.
Keywords: transkriptom; RNA, Messenger; Inosine; Epigenomics; RNA Processing, Post-Transcriptional; ADAR; posttranskripční úpravy RNA; epigeneze genetická; Transcriptome; epitranscriptome; epigenomika; m6A; Animals; lidé; m1A; Humans; zvířata; pseudouridine; m6Am; m5C; messenger RNA; Epigenesis, Genetic